2018
DOI: 10.33137/ijidi.v2i1/2.32209
|View full text |Cite
|
Sign up to set email alerts
|

Holy selfies: Performing pilgrimage in the age of social media

Abstract: In this article, we examine the selfie-taking and sharing practices of Muslim pilgrims in Mecca, Saudi Arabia. We introduce the concept of the “holy selfie” (a selfie taken during either theHajj or the Umrah pilgrimages) and report on a visual content analysis of a sample of 100 holy selfies publicly available on social networking platforms. We seek to reach an understanding of the work that holy selfies do in the context of the expressions of spiritual and religious identity of those producing them. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 25 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…These documentary practices not only have private but also public meanings. This is evidenced in Caidi, Beazley and Marquez's (2018) study of holy selfies. The authors suggest that holy selfies facilitate interactions between Muslims and non-Muslims in a manner close to communitas.…”
Section: Pilgrimage and Homementioning
confidence: 80%
“…These documentary practices not only have private but also public meanings. This is evidenced in Caidi, Beazley and Marquez's (2018) study of holy selfies. The authors suggest that holy selfies facilitate interactions between Muslims and non-Muslims in a manner close to communitas.…”
Section: Pilgrimage and Homementioning
confidence: 80%
“…In the extant literature, it is suggested that pilgrims experience various forms of social pressures (Caidi et al, 2018). These include pressures from their responsibilities back home, pressures surrounding the tension between consumerism and spirituality (Caidi et al, 2018), and pressures from other pilgrims on how one should behave.…”
Section: Social Pressuresmentioning
confidence: 99%
“…While on the spur of the moment he obviously felt justified in addressing malpractice, it cannot be excluded that in hindsight he might feel somewhat uncomfortable about his appearance in this video; the anger he showed does not match the expectations that people have of someone who has performed the pilgrimage and who is supposed to have been transformed by the spiritual experience. Moreover, although self-presentation does play a role in many postings of pilgrims on social media (see, e.g., Caidi, Beazley, and Colomer Marquez, 2018), it was most probably not this pilgrim's main concern when he addressed a wider Moroccan audience in the video. In fact, his contribution to a narrative that counters Morocco's mainstream national representation of the hajj was the outcome of unintended disclosure.…”
Section: Introduction1mentioning
confidence: 99%